DOSTOSOWANIE POLSKIEGO PRAWA DO EUROPEJSKICH STANDARDÓW W ZAKRESIE UBEZPIECZENIA OC POSIADACZY POJAZDÓW MECHANICZNYCH - Ludwichowska, Katarzyna (Zeszyty Prawnicze, 2017)
Adaptation of Polish Motor Liability Insurance Law to EU Standards Summary The study begins with general remarks concerning the role of civil liability insurance in respect of the use of m otor vehicles as an instrument reducing the negative effects of road accidents, as well as remarks concerning the Green Card System and EU M otor Insurance Directives. Further, the most im portant provisions of EU Directives on Motor Insurance are presented and the Polish law is compared with the EU standards. Amongst other things, the following issues are discussed: checks on insurance againt civil liability in respect of the use of m otor vehicles, the m inim um amounts of insurance cover, compensation in the event o f an accident caused by an uninsured or unidentified vehicle, territorial scope of insurance protection, freedom to provide services in the field o f motor liability insurance and the legal means constituting a so called „System of the Fourth M otor Insurance Directive”. The final remarks concern the draft of the Fifth EU Directive on M otor Insurance and the changes in Polish law that will be necessary after the adoption of that directive.